Impact Of Dual Banking System On Financial Performance Sharia Bank In Indonesia : Study Of Literature And Perspectives Of Postgraduate Students In Sharia Economy (Pena Cendekia Insani, 2022)
The economy is one of the many sectors that have a very important role in the life of a country. In the case of Indonesia in the micro economy, banking plays a role as a source of financing, while in the macro (global) economy, banking contributes greatly to economic growth and controlling inflation. Economic growth and banking activities are of course interconnected in such a way that the growth of the banking sector is influenced by the conditions of economic growth itself. About sharia banking, Law Number 21/2008 in its article contains that sharia banking is everything related to sharia business units in sharia banks, including groups/institutions, business activities, as well as ways and processes of running a business based on the principles of sharia banking. -Sharia principles consist of Sharia Commercial Banks (BUS) and Sharia People's Financing Banks (BPRS). With this dual banking system, it is intended that banking institutions can carry out dual operational activities at the same time, namely interest-based banks and non-interest-based banks. Banks that transform their systems with sharia principles will automatically adopt sharia principles in their operational activities. Meanwhile, for banks whose operations are both carried out at the same time, the technical operations are regulated in such a way, especially considering the interaction of interest-based activities, which is different from the concept of Islamic banking, whose activities are free of interest so that the two can, of course, be distinguished. The implementation of the Dual banking system has in indicators of the financial performance of Islamic banks such as CAR, ROA, NPF, FDR, and BOPO to become the focus of this research when the dual system is carried out side by side. Profitability, of course, cannot be ruled out from every business activity that is carried out, including Islamic banking. FDR and ROA are very important financial indicators in bank performance and have a direct impact on the bank's business, including Islamic banks.